2009
DOI: 10.1007/s00421-009-1052-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined exercise and gravity transients and apnea on hemodynamics

Abstract: Hemodynamic responses to combined heavy dynamic leg exercise (hiP), breath holding (BH) and gravity-induced blood volume shifts direction were studied. Thirteen subjects were studied at normal gravity and 12 during parabolic flight, performing 20 s hiP or combined hiP&BH (stimulus period) from a baseline of 30 W at normal gravity (1 G(z+)). Heart rate and mean arterial pressure responses to BH were similar between gravity conditions, but stroke volume (SV) differed markedly between gravity conditions: at 1 G(z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In a recent study, Caiani et al (2006) used 3-D echocardiography in subjects who were sitting on a saddle during parabolic Xight, and reported a 20% increase in SV after the transition into microgravity. Other parabolic Xight studies, using impedance cardiography (HoVmann et al 2009) or inert gas rebreathing (Norsk et al 2006) have provided similar results, showing a 20-30% increase in SV after entering weightlessness in the upright seated position. In one study, Lathers et al (1989) reported that estimated SV increases up to 60% in standings subjects after exposure to transient microgravity, which is in line with our Wndings of an average 45% increase in SV.…”
Section: Validity Of Methodssupporting
confidence: 52%
See 1 more Smart Citation
“…In a recent study, Caiani et al (2006) used 3-D echocardiography in subjects who were sitting on a saddle during parabolic Xight, and reported a 20% increase in SV after the transition into microgravity. Other parabolic Xight studies, using impedance cardiography (HoVmann et al 2009) or inert gas rebreathing (Norsk et al 2006) have provided similar results, showing a 20-30% increase in SV after entering weightlessness in the upright seated position. In one study, Lathers et al (1989) reported that estimated SV increases up to 60% in standings subjects after exposure to transient microgravity, which is in line with our Wndings of an average 45% increase in SV.…”
Section: Validity Of Methodssupporting
confidence: 52%
“…Thus, direct comparisons of this kind for validation purposes are limited in so far that they require steady state conditions. Alternative methods for the non-invasive tracking of changes in SV during parabolic Xight can be obtained by ultrasound (Caiani et al 2006;Iwase et al 1999) or electrical impedance cardiography (Lathers et al 1989;HoVmann et al 2009). In a recent study, Caiani et al (2006) used 3-D echocardiography in subjects who were sitting on a saddle during parabolic Xight, and reported a 20% increase in SV after the transition into microgravity.…”
Section: Validity Of Methodsmentioning
confidence: 99%
“…For the FB150 stimulus the high ΔMAP reaction of the BB-Mono group must be mentioned. However, the typical responses are generally in line with reported reactions [4,13,14,38]. More pronounced ΔHR reactions were identified in the BB-Mono group if high WR was involved.…”
supporting
confidence: 85%
“…It is an accepted explanation that the reason for these reactions is an oxygen conserving effect [19] in the periphery to improve the oxygen delivery to brain, heart and other central organs. Apnea in combination with a simultaneous increase in work rate (WR) results in an initial rise of HR, followed by a decrease after approximately 10 s, accompanied by a continuous rise in MAP and TPR [4,13,14,38]. Additionally, Hoffmann et al [14] found increases in stroke volume (SV) in dry conditions, as well as Marongiu et al [24], during free diving in the sea.…”
Section: Introduction ▼mentioning
confidence: 99%
See 1 more Smart Citation